Angular distribution and asymmetries in flavor-changing neutral-current decay B → K* l⁺ l⁻ - Korchin, A.Yu.; Kovalchuk, V.A.; Lazarenko, D.O. (Вопросы атомной науки и техники, 2012)
The fully differential angular distribution for the rare flavor-changing neutral current decay Bd⁰ → K*⁰( → K⁻π⁺)e⁺e⁻ is studied. The emphasis is placed on accurate treatment of the contribution from the processes Bd⁰ → K*⁰( → K⁻π⁺)V with intermediate vector resonances V = ρ(770), ω(782), φ(1020), J/ψ, ψ(2S), … decaying into the e⁺e⁻ pair. The two versions of the vector-meson-dominance model for the transition Vγ are used and tested. The branching ratio, longitudinal polarization fraction of the K*⁰ meson, transverse asymmetry AT⁽²⁾ and forward-backward asymmetry are compared with data from BaBar and CDF, and predictions for experiments at LHCb and B factories are made.